2019
DOI: 10.1002/asia.201900422
|View full text |Cite
|
Sign up to set email alerts
|

Substitution‐Pattern‐ and Counteranion‐Depending Ion‐Pairing Assemblies Based on Electron‐Deficient Porphyrin–AuIII Complexes

Abstract: Porphyrin–AuIII complexes, which were partially or totally modified with C6F5 at the meso positions, were synthesized. The highly electron‐withdrawing substituents induced electron‐deficient states and Lewis acid properties. Single‐crystal X‐ray analysis of the ion pairs revealed ion‐pairing assemblies with characteristics dependent on the number and substitution pattern of the C6F5 units and the geometries of the anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…19a), in order to control the electronic states and resulting ion-pairing assemblies. 54 The electron-deficient character of C 6 F 5 -substituted porphyrin-Au III complexes was confirmed by electrostatic potential (ESP) diagrams, suggesting that the electron deficiency of the porphyrin core increases with the introduction of C 6 F 5 units (Fig. 19b).…”
Section: -3 Metal Complexes Of π-Electronic Ligands For π-Electronimentioning
confidence: 90%
See 1 more Smart Citation
“…19a), in order to control the electronic states and resulting ion-pairing assemblies. 54 The electron-deficient character of C 6 F 5 -substituted porphyrin-Au III complexes was confirmed by electrostatic potential (ESP) diagrams, suggesting that the electron deficiency of the porphyrin core increases with the introduction of C 6 F 5 units (Fig. 19b).…”
Section: -3 Metal Complexes Of π-Electronic Ligands For π-Electronimentioning
confidence: 90%
“…This type of electron-withdrawing character of peripheral substituents is crucial for tuning interionic interactions. 54 3-6. Aliphatic porphyrin-Au III complexes for dimensioncontrolled assemblies Introduction of aliphatic long alkyl chains into an appropriate π-electronic unit affords soft materials comprising the stacking core π-units supported by van der Waals interactions of alkyl chains.…”
Section: -3 Metal Complexes Of π-Electronic Ligands For π-Electronimentioning
confidence: 99%
“…Porphyrins with metal ions in d 8 electronic configuration can function as charged π-electronic systems because they require no axial ligand coordination. On the basis of the synthesis strategy of charged π-electronic systems, we found that the porphyrin–Au III complexes and divalent metal complexes of oxophlorins (deprotonation states of meso -hydroxy-substituted porphyrins) , act as π-electronic cations and anions, respectively, for ion-pairing assemblies (Figure c). Porphyrin ion pairs can be obtained from various derivatives through peripheral modifications of the charged porphyrin skeletons, resulting in interesting electronic properties and functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…The meso ‐substituents of porphyrin–Au III complexes are also important for controlling the ion‐pairing assembled structures. Porphyrin–Au III complexes that are partially substituted with meso ‐pentafluorophenyl units, including 5,10,15‐trisubstituted 1 b + , display the electron‐deficient properties and solid‐state columnar structures, depending on substitution patterns . Single‐crystal X‐ray analysis of the ion pair 1 b + ‐ 2 c ⋅Cl − reveals a solid‐state ion‐pairing assembly .…”
Section: Figurementioning
confidence: 99%
“…A two‐by‐two charge‐by‐charge columnar structure is observed (Figure b,c), in which dimeric stacking of 1 b + has a stacking distance of 3.25 Å between the porphyrin mean planes (Figure d). This dimeric structure is also observed in the solid states of 1 b + ‐Cl − and 1 b + ‐PF 6 − , wherein two 1 b + are stacked in reversed orientation, cancelling the dipole moments . The Cl − ⋅⋅⋅Cl − distance in the column is 3.98 Å (Figure a), suggesting that the electrostatic repulsion between two Cl − can be overcome by hydrogen‐bonding and electrostatic interactions between 2 c 2 ⋅Cl − 2 with two 1 b + , as revealed by the ESP diagram calculated at B3LYP/6‐31+G(d,p) with LanL2DZ for Au based on the crystal structure .…”
Section: Figurementioning
confidence: 99%